Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0970-4388.121831
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of total salivary secretory immunoglobulin A (SIgA) and mutans specific SIgA in children having different caries status

Abstract: The mutans specific SIgA and total SIgA has a weak, but negative correlation in children potentiating caries inhibitory action of SIgA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Various studies reported contradictory results on the correlation between sIgA and dental caries [17,20]. The same results were also found in this study.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Various studies reported contradictory results on the correlation between sIgA and dental caries [17,20]. The same results were also found in this study.…”
supporting
confidence: 85%
“…Many researchers reported the correlation between sIgA and ECC cases, but it is still contradictory and inconsistent. Pal et al in their study reported that caries-free children had higher sIgA level than caries children [17], indicating the effective defense function of sIgA in caries-free individuals [18]. In contrast, Bagherian & Asadikaram (2012) [19] and Priyaet a.l (2013) [20] in their research reported different results, that children with caries had higher sIgA level compared to caries-free children.…”
mentioning
confidence: 98%
“…It can prevent the invasion and adhesion of pathogens, and can bind the corresponding antigen to inhibit bacterial proliferation and neutralize toxins, and can resist proteolytic enzymes. Protect the intestinal mucosa from being digested, and exert local anti-infection and anti-allergic effects ( Pal et al, 2013 ; Zhang J. et al, 2020 ).…”
Section: Effect Of Severe Acute Respiratory Syndrome Coronavirus 2 On Human Intestinal Tractmentioning
confidence: 99%
“…The results of the correlation between salivary s-IgA levels and the severity of dental caries were shown in Figure 5. Because of the limited number of studies on Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20203208/899106/bsr-2020-3208.pdf by guest on 14 December 2020 differences in the severity of caries (only 9 studies were included) [21,25,5,33,36,38,39,41,46], and the heterogeneity in the studies was greater than 50% (I 2 >50%), a random-effects model was used (P <0.001). The results show that when comparing the salivary s-IgA levels of patients with high dental caries and patients with low dental caries ( Figure 5A), we found that the salivary s-IgA levels of patients with high dental caries were significantly lower than those of patients with low dental caries (SMD=-…”
Section: The Relationship Between the Saliva S-iga Level And The Sevementioning
confidence: 99%
“…with acceptable heterogeneity (I 2 =46%).The 22, 25, 27, 5,32,33,34,38,39,44,45,46,47,48 caries-free healthy control group included 265 study subjects and the caries group included 410 study subjects, and the combined meta-analysis of caries activity was performed at lower levels of s-IgA (SMD=-1.23, 95%CI: [-1.48; -0.99], P<0.001). In the sensitivity analysis, the removal of any individual study did not change the overall statistical significance, indicating that the meta-analysis was relatively stable and reliable (Figure 7).…”
mentioning
confidence: 99%